Freedom Through Education - Coffman, Lotus Delta, 1875-1938 (Book collections on Project MUSE., 1939)
Freedom Through Education was first published in 1939. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. February 15, 1939To the People of Minnesota:Knowing President Coffman as well as I did, I know he would have deprecated any elaborate eulogy of his work in and for the University of Minnesota. I know also that he welcomed always any opportunity to present his though about it and his reflections on the changing world that conditioned the flexible and for.